(Re)construction of valentine’s day on social media platforms: a study of messages circulating on whatsapp around valentine’s day. - Mutsinze, Jane Tadiwa (Midlands State University, 2018)
Holidays seem natural and yet every now and then their courses seem to change; how they are celebrated has proved not to be a stable state but fluid with the passing of time. My dissertation addresses the question of how holidays are not state but fluid; what is it that influences their instability to a particular celebration course. Firstly it is to be noted that holidays are not natural in any way, instead they are a result of a societal construct, which goes to support Gergen (1994), who is of the view that social constructionism theory is a reminder of how values, ideologies and social institutions are human-made and not natural. My argument is that the society manipulates language in the construction of any holiday, and so language is at the core of the construction to any holiday. Burr (1995) contends that the basis for all our thoughts is provided for by language, thus language becomes a means to expressing how one feels; in the construction of worldviews and realities language is the vehicle used. The relationship between the society and language in constructing realities is better understood by applying the Social Construction theory; which was developed so as to demonstrate how reality is as a result of social construction and not naturally given; Social constructionists adopt a relativistic view of reality (Denzin and Lincoln 2000 p.10). My dissertation’s focus is on the role language plays in the (re) Construction or construction of any holiday, by looking at how Valentines’ celebration for 2015 has been (re) constructed, main focus being the analysis of the messages that circulated on Whatsapp on Valentines’ celebration. Holidays are (re) constructed because of current needs that ought to be met; be it economic, social, religious or political factors.